1991
DOI: 10.1063/1.529476
|View full text |Cite
|
Sign up to set email alerts
|

The Dirac equation in external fields: Variable separation in Cartesian coordinates

Abstract: The method of separation of variables in the Dirac equation proposed in an earlier work by one of the present authors [J. Math. Phys. 30, 2132 (1989)] is developed for the complete set of interactions of the Dirac particle. The essence of the method consists of the separation of the first-order matrix differential operators that define the dependence of the Dirac bispinor on the related variables, but commutation of such operators with or between the operator of the equation is not assumed. This approach, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Several contributions to the search for exact solutions of the Dirac equation in curved spaces may be found in Bagrov and Gitman [2] and Cook [18]. In Shishkin [30,31] and Shiskin et al [1,32,33] an algebraic procedure is developed to obtain separation relations for the solution of the Dirac equation. The definition of separation used therein coincides essentially with our definition of "naive separation" [26] in dimension two.…”
Section: Introductionmentioning
confidence: 99%
“…Several contributions to the search for exact solutions of the Dirac equation in curved spaces may be found in Bagrov and Gitman [2] and Cook [18]. In Shishkin [30,31] and Shiskin et al [1,32,33] an algebraic procedure is developed to obtain separation relations for the solution of the Dirac equation. The definition of separation used therein coincides essentially with our definition of "naive separation" [26] in dimension two.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of relativistic particles obeying the covariant Dirac equation in RobertsonWalker space-time has been discussed in various contexts [1][2][3][4][5][6][7][8]. One of the most important but difficult problems of the quantum field theory in curved spacetime is the problem of finding analytic solutions of Dirac equation on given backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of articles devoted to the study of this problem is scarce, the reason is that, for solving the Dirac equation, as general rule, a complete separation of variables is required and, the inclusion of tensor field functions in the Dirac equation dramatically restricts the possibilities of separation of variables [2][3][4][5] In this case, the possibilities are even more limited that those obtained for the Dirac equation minimally coupled to the electromagnetic field 6 , or in the presence of gravitational fields 7 This one is because the gravitational field goes into the Dirac equation in a geometric way, via the Lame's coefficients, and no additional matrices in the equation if we choose to work in a diagonal tetrad gauge. Regarding the vector electromagnetic fields, the inclusion of them in the Dirac equation via the generalized momentum (minimal coupling), does not conduce to the apparition of new matrices, and 6 the presence of tensor fields terms of the form gγ m γ n T mn introduces in the Dirac equation a new functional dependence.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulties that arise are those we find when we include non geometrized fields like scalar, pseudo-scalar or pseudo-vector fields. 4,5,8 Now, we proceed to mention the most relevant exact solutions of the Dirac equation with anomalous moment reported in the literature, among them we have the constant magnetic field problem solved by Strocchi 9 and by Ternov et al 10 , a generalization of the Volkov's problem was found by Ternov et al 11,12 , and more recently this problem has been revisited by Barut 13 . The problem in spherical coordinates for the central field has been studied by Ternov 14 and Barut 15,16 , a good review on exact solutions of the Dirac equation with anomalous interaction can be found in 17 .…”
Section: Introductionmentioning
confidence: 99%